Unfinished revolutions Yemen, Libya, and Tunisia after the Arab Spring - Fraihat, Ibrahim (Yale University Press, 2016)
This book is based on the original field research Fraihat conducted over three years in Yemen, Libya, and Tunisia. It is the result of over 200 interviews with key figures including senior government officials, heads of political parties, revolutionary youth activists, former regime loyalists, representatives of women's and civil society organizations, military and militia commanders, tribal leaders, and members of displaced communities.